PAD2-Mediated Citrullination Contributes to Efficient Oligodendrocyte Differentiation and Myelination - Falcão, Ana Mendanha; Meijer, Mandy; Scaglione, Antonella; Rinwa, Puneet; Agirre, Eneritz; Liang, Jialiang; Larsen, Sara C.; Heskol, Abeer; Frawley, Rebecca; Klingener, Michael; Varas-Godoy, Manuel; Raposo, Alexandre A.S.F.; et al. (Cell reports (Cambridge), 2019)
Citrullination, the deimination of peptidylarginine residues into peptidylcitrulline, has been implicated in the etiology of several diseases. In multiple sclerosis, citrullination is thought to be a major driver of pathology through hypercitrullination and destabilization of myelin. As such, inhibition of citrullination has been suggested as a therapeutic strategy for MS. Here, in contrast, we show that citrullination by peptidylarginine deiminase 2 (PAD2) contributes to normal oligodendrocyte differentiation, myelination, and motor function. We identify several targets for PAD2, including myelin and chromatin-related proteins, implicating PAD2 in epigenomic regulation. Accordingly, we observe that PAD2 inhibition and its knockdown affect chromatin accessibility and prevent the upregulation of oligodendrocyte differentiation genes. Moreover, mice lacking PAD2 display motor dysfunction and a decreased number of myelinated axons in the corpus callosum. We conclude that citrullination contributes to proper oligodendrocyte lineage progression and myelination. [Display omitted] •PAD2 is increased upon OL differentiation•OL differentiation is facilitated by PAD2-mediated chromatin remodeling in myelin genes•PAD2 contributes to efficient myelination and motor and cognitive functions•Nuclear and myelin proteins interact and are citrullinated by PAD2 Falcão et al. demonstrate that PAD2-mediated citrullination, the conversion of peptidylarginine into peptidylcitrulline, has two roles in oligodendrocyte cells. In the nucleus, PAD2 acts as a chromatin modifier contributing to efficient oligodendrocyte precursor cell differentiation, while in the cytoplasm PAD2 is required for proper oligodendrocyte myelination.